Aspects of the physiology of the South African abalone, Haliotis Midae L., and implications for intensive abalone culture - Lyon, Robert Gary (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1996)
A physiological study was carried out to determine the effects of temperature, quantity of food fed, feeding activity and size class on the oxygen consumption and ammonia production of the South African abalone Haliotis midae L.. A set of intermittent flow respirometer chambers were used in a recirculating system to measure the oxygen consumption rates of fed (postprandial) and unfed (postabsorptive) abalone for three different size classes (15, 30, and 50mm) at three different temperatures (16Â°, 20Â° and 23Â°C) over a 24 hour period. Ammonia production rates and food consumption rates were simultaneously determined. Oxygen consumption and Ammonia production rates per gram abalone were linear functions of abalone size, temperature, and mass of food consumed. Oxygen consumption and ammonia production rates were found to increase proportionally to temperature and in inverse proportion to abalone size. These rates were significantly higher for fed as opposed to unfed abalone. Equations were derived to predict oxygen consumption and ammonia production for fed and unfed animals for a range of temperatures and size classes of abalone. A 96h LC50 lethal toxicity test for exposure to ammonia established 1.08mg.1â »Â¹ of unionised ammonia as the lethal limit. A test on the long term effects on growth of acute exposure (12h) to various sublethal concentrations of ammonia showed no significant effects on growth for concentrations below 0.88 mg.1â »Â¹. A safe chronic exposure level of 0.02 mg.1Â¹ NHâ‚ƒ-N was used to predict optimal flow rates required per kilogram of abalone in a rearing tank over a range of size classes and temperatures. The physiological and biological requirements of H. midae and the implications of this knowledge for rearing tank management and optimal design are discussed.
Keywords: Abalones -- Physiology; Abalone culture